Food, fermentation, and micro-organisms - Bamforth, Charles W.; Cook, David J. (Wiley Blackwell, 2019)
Fermentation and the use of micro-organisms is one of the most important aspects of food processing – an industry that is worth billions of US dollars world-wide. Integral to the making of goods ranging from beer and wine to yogurt and bread, it is the common denominator between many of our favorite things to eat and drink. In this updated and expanded second edition of Food, Fermentation, and Micro-organisms, all known food applications of fermentation are examined. Beginning with the science underpinning food fermentations, the author looks at the relevant aspects of microbiology and microbial physiology before covering individual foodstuffs and the role of fermentation in their production, as well as the possibilities that exist for fermentation's future development and application. Many chapters, particularly those on cheese, meat, fish, bread, and yoghurt, now feature expanded content and additional illustrations. Furthermore, a newly included chapter looks at indigenous alcoholic beverages. Food, Fermentation, and Micro-organisms, Second Edition is a comprehensive guide for all food scientists, technologists, and microbiologists working in the food industry and academia today. The book will be an important addition to libraries in food companies, research establishments, and universities where food studies, food science, food technology and microbiology are studied and taught.